Application of the DeLone and McLean’s model to assess the effectiveness of an intranet in an open distance learning library - Rammutloa, Modiehi Winnie (Stellenbosch : Stellenbosch University, 2017)
Thesis (MPhil)--Stellenbosch University, 2017.